Structured Triacylglycerol with Optimal Arachidonic Acid and Docosahexaenoic Acid Content for Infant Formula Development: A Bio-Accessibility Study - Vázquez, Luis; Pardo de Donlebún, Blanca; Gutiérrez-Guibelalde, Alejandra; Chabni, Assamae; Torres, Carlos F. (Foods, 2024)
Polyunsaturated fatty acids (PUFAs), especially arachidonic acid (ARA) and docosahexaenoic acid (DHA), are extremely important fatty acids for brain development in the fetus and early childhood. Premature infants face challenges obtaining these two fatty acids from their mothers. It has been reported that supplementation with triacylglycerols (TAGs) with an ARA:DHA ( w / w ) ratio of 2:1 may be optimal for preterm infants, as presented in commercial formulas such as Formulaid™. This study explored methods to produce TAGs with a 2:1 ratio (ARA:DHA), particularly at the more bioavailable sn -2 position of the glycerol backbone. Blending and enzymatic acidolysis of microalgae oil (rich in DHA) and ARA-rich oil yielded products with the desired ARA:DHA ratio, enhancing sn -2 composition compared to Formulaid™ (1.6 for blending and 2.3 for acidolysis versus 0.9 in Formulaid™). Optimal acidolysis conditions were 45 °C, a 1:3 substrate molar ratio, 10% Candida antarctica lipase, and 4 h. The process was reproducible, and scalable, and the lipase could be reused. In vitro digestion showed that 75.5% of the final product mixture was bio-accessible, comprising 19.1% monoacylglycerols, ~50% free fatty acids, 14.6% TAGs, and 10.1% diacylglycerols, indicating better bio-accessibility than precursor oils.